Alkaloids from the stem barks of Scutia buxifolia Reissek (Rhamnaceae): Structures and antimicrobial evaluation. (April 2022) - Dahmer, Janice; Marangon, Patricia; Adolpho, Luciana O.; Reis, Frederico L.; Maldaner, Graciela; Burrow, Robert A.; Mostardeiro, Marco A.; Dalcol, Ionara I.; Morel, Ademir F.
Abstract: A reinvestigation of the chemical constituents of the stem barks of Scutia buxifolia, a member of the Rhamnaceae, resulted, along with the known alkaloids scutianine C and scutianene L, in the isolation of three undescribed diastereoisomeric alkaloids – scutianine N, 27- epi -scutianine N and 3, 4, 7-tri- epi -scutianine N –, one undescribed non macrocyclic alkaloid – scutianine Q – and a neutral compound –scutianene M. Their structures were determined using extensive NMR techniques and HRMS. The absolute configurations of the stereogenic centers of the three diastereoisomeric alkaloids have been assigned by gas chromatography employing modified cyclodextrins as chiral stationary phases. Scutianine Q had its structure and stereochemistry defined by single crystal X-ray crystallographic analysis. All tested compounds showed good to moderate antibacterial activity (MICs between 1.56 and 100 μg mL-1) when evaluated in vitro against a panel of Gram-positive and Gram-negative bacteria. Some stereochemistry-activity relationships have been identified for the antibacterial activity of diastereoisomeric alkaloids against the Gram-negative bacteria Enterobacter aerogenes . The alkaloid 27- epi -scutianine N was as active as the standard antibiotic chloramphenicol (MIC = 1.56 μg mL-1), while scutianine N and 3, 4, 27-tris- epi -Scutianine N were inactive (>100 μg mL-1). Graphical abstract: Image 1 Highlights: Five undescribed alkaloids from Scutia buxifolia stem barks. Scutianine N, 27- epi -scutianine N, 3, 4, 7-tri- epi -scutianine N, scutianine Q and scutianene M. Absolute configuration. Scutia buxifolia alkaloids antimicrobial activity.